Die design for oil seperator plates used in Gen-2 campro engine / Abdul Halim Ismail - Ismail, Abdul Halim (2005)
In this report, chapter 1 addresses the introduction to the project. It deals with the brief definition of pressworking and die. Apart from that, the objectives of this project are described as well as the scope of project. Chapter 2 introduces the pressworking design. It includes the operations of the pressworking and its basic process. The type of dies and its components is presented in chapter 3. All of the components described are based on the generally used components in the designing of die for pressworking. Chapter 4 puts forward the die design procedures. In this chapter, all the relevant equations that are important to be considered in designing die are defined. The way of locating die components also described in this chapter. Chapter 5 presents the design die for oil separator plates. It relates what have been discussed in previous chapters and hence the design of die for the parts is shown. The design of the inspection jig for oil separator plate is presented in chapter 6. It includes the consideration taken and thus the design of the jig for the part. The conclusion is provided in chapter 7.